Multimodal Probe Based on ISFET Electrochemical Microsensors for In-Situ Monitoring of Soil Nutrients in Agriculture - Matthieu Joly; Laurent Mazenq; Maurane Marlet; Pierre Temple-Boyer; Céline Durieu; Jérôme Launay (Proceedings, 2017)
We report the design of a silicon chip dedicated to the in-situ monitoring of soil nitrogen cycle in wheat crop. Our study shows that ion-sensitive field effect transistor (ISFET) microsensors are suitable for quick on-site or long-term analysis of nutrients measured directly in soil as opposed to soil extracts analysis. Our pH-ISFET recorded soil pH for six months with results in good accordance with standard sampling method and without any loss of sensitivity. The adaptation of pH-ISFET in pNO3 and pNH4-ISFET allowed, for the first time, the in-situ measurements of natural variations of soil nitrogen contents caused by microorganisms’ activity